Optimal extent of completion lymphadenectomy for patients with melanoma and a positive sentinel node in the groin. Issue 1 (2nd November 2017) - Verver, D; Madu, M F; Oude Ophuis, C M C; Faut, M; de Wilt, J H W; Bonenkamp, J J; Grünhagen, D J; van Akkooi, A C J; Verhoef, C; van Leeuwen, B L
Abstract: Background: The optimal extent of groin completion lymph node dissection (CLND) (inguinal or ilioinguinal dissection) in patients with melanoma is controversial. The aim of this study was to evaluate whether the extent of groin CLND after a positive sentinel node biopsy (SNB) is associated with improved outcome. Methods: Data from all sentinel node-positive patients who underwent groin CLND at four tertiary melanoma referral centres were retrieved retrospectively. Baseline patient and tumour characteristics were collected for descriptive statistics, survival analyses and Cox proportional hazards regression analyses. Results: In total, 255 patients were included, of whom 137 (53·7 per cent) underwent inguinal dissection and 118 (46·3 per cent) ilioinguinal dissection. The overall CLND positivity rate was 18·8 per cent; the inguinal positivity rate was 15·5 per cent and the pelvic positivity rate was 9·3 per cent. The pattern of recurrence, and 5-year melanoma-specific survival, disease-free survival and distant-metastasis free survival rates were similar for both dissection types, even for patients with a positive CLND result. Cox regression analysis showed that type of CLND was not associated with disease-free or melanoma-specific survival. Conclusion: There was no significant difference in recurrence pattern and survival rates between patients undergoing inguinal or ilioinguinal dissection after a positive SNB, even after stratification for a positive CLND result. An inguinal dissection is a safe first approach as CLND in patients with a positive SNB. Abstract : Inguinal is enough